Effectiveness of supine/standing urinalysis for differential diagnosis of left renal vein entrapment syndrome combined with or without glomerulopathy. Issue 6 (June 2014) - Jin, Meiling; Hu, Panpan; Ding, Rui; Chen, Pu; Qiu, Qiang; Wu, Jie; Liu, Shuwen; Xie, Yuansheng; Chen, Xiangmei
Abstract Aim To assess the effectiveness of supine/standing urinalysis for differential diagnosis of left renal vein entrapment syndrome (LRVES) combined with or without glomerulopathy. Methods The enrolled patients with abnormal urinalysis and LRVES demonstrated by Doppler sonography were guided to perform a supine/standing urinalysis. Results Fifty‐two patients were enrolled. Most of them were adolescents (aged 14–29 years, 73.1%) and with low body mass index (BMI, mean BMI, 19.8 ± 2.4 kg/m2). Seventeen cases (32.7%) manifested orthostatic urine abnormalities (OUA, proteinuria and/or haematuria show negative in supine while positive after 15 min standing), two patients who had undergone renal biopsies both showed no evidence of kidney lesions, another two patients were changed from abnormal to normal urinalysis after weight gain. The remaining 35 cases (67.3%) manifested non‐orthostatic urine abnormalities (NOUA, proteinuria and/or haematuria show positive both in supine and standing), 15 patients had undergone renal biopsies and showed different degrees of glomerulopathy. After prednisone/immunosuppression therapy, four patients with glomerulonephritis were changed from the NOUA to the OUA classification. Statistics analyses showed that serum total protein and albumin levels were significantly lower (P = 0.028, 0.007, respectively) and urinary protein was significantly higher (P = 0.007) in the NOUA group than in the OUA group. Conclusion After the indication of LRVES by ultrasound, patients with OUA likely have only LRVES, while patients with NOUA likely also have glomerulopathy. Supine/standing urinalysis combined with Doppler sonography can be helpful for differential diagnosis of LRVES combined with or without glomerulopathy.